Release of Iron-Loaded Ferritin in Sodium Iodate-Induced Model of Age Related Macular Degeneration: An In-Vitro and In-Vivo Study - Ajay Ashok; Suman Chaudhary; Aaron S. Wise; Neil A. Rana; Dallas McDonald; Alexander E. Kritikos; Ewald Lindner; Neena Singh (Antioxidants, 2021)
In this report, we evaluated the role of iron in sodium iodate (NaIO3)-induced model of age-related macular degeneration (AMD) in ARPE-19 cells in-vitro, and mouse models in-vivo. ARPE-19 cells, a human retinal pigmented epithelial cell line, were exposed to 10 mM of NaIO3 for 24 h, and the expression and localization of major iron modulating proteins was evaluated by Western blotting (WB) and immunostaining. Synthesis and maturation of cathepsin-D (cat-D), a lysosomal enzyme, was evaluated by quantitative reverse-transcriptase polymerase chain reaction (RT-qPCR) and WB respectively. For in-vivo studies, C57BL/6 mice were injected with 40 mg/kg mouse body weight of NaIO3 intraperitoneally, and their retina was evaluated after 3 weeks as above. We observed that NaIO3 induced a 10-fold increase in ferritin in ARPE-19 cells, which co-localized with LC3II, an autophagosomal marker, and LAMP-1, a lysosomal marker. A similar increase in ferritin was noted in retinal lysates and retinal sections of NaIO3-injected mice by WB and immunostaining. Impaired synthesis and maturation of cat-D was also noted. Accumulated ferritin was loaded with iron, and released from retinal pigmented epithelial (RPE) cells in Perls’ and LAMP-1 positive vesicles. These observations suggest that NaIO3 impairs lysosomal degradation of ferritin by decreasing the transcription and maturation of cat-D in RPE-19 cells. Iron-loaded ferritin accumulates in lysosomes and is released in lysosome membrane-enclosed vesicles in the extracellular milieu. Accumulation of ferritin in RPE-19 cells and fusion of ferritin-containing vesicles with adjacent photoreceptor cells is likely to create iron overload, compromising their viability. Moreover, reduced activity of cat-D is likely to promote the accumulation of other cellular debris in lysosomal vesicles, contributing to AMD-like pathology.